2013
DOI: 10.1038/bjc.2013.274
|View full text |Cite
|
Sign up to set email alerts
|

Both STAT1 and STAT3 are favourable prognostic determinants in colorectal carcinoma

Abstract: Background:Aberrant activities of Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling pathways have been implicated in the development and spread of various cancer entities, among them colorectal carcinoma (CRC). Transcription factors STAT3 and STAT1, both downstream effectors of interleukin (IL)-6 and its receptor, are involved in growth and developmental control of CRC cells. Constituents of the signalling network around IL-6 and STAT activation are discussed as potential bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 36 publications
5
92
1
1
Order By: Relevance
“…6E). Importantly, our findings may explain the accumulating controversies regarding the tumor suppressor function of STAT3 in various cancer types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, there are many publications in which the immune-detection of pSTAT3 Y705 or nuclear STAT3 was found to significantly correlate with a better outcome (9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…6E). Importantly, our findings may explain the accumulating controversies regarding the tumor suppressor function of STAT3 in various cancer types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, there are many publications in which the immune-detection of pSTAT3 Y705 or nuclear STAT3 was found to significantly correlate with a better outcome (9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 64%
“…The oncogenic potential of STAT3 has been well documented; specifically, the constitutively activated STAT3 mutant (commonly labeled STAT3C) can effectively induce malignant transformation (4), and many human cancers harbor constitutively active STAT3 (1)(2)(3). Nevertheless, accumulating evidence from both experimental and clinical studies has suggested that STAT3 may also carry a tumor suppressor role in specific contexts (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). For instance, in a mouse model of intestine adenoma, tissue-specific STAT3 gene knockout was found to enhance tumor invasion and promote tumor progression (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported oncogenic effects of elevated STAT3 signalling (30)(31)(32)(33)(34)(35)(36). In contrast, others reported on STAT3 as a determinant of positive outcome in intestinal tumour progression (37,38). Moreover, we could show recently that absence of STAT1 and/ or STAT3 proteins is correlated with shorter survival of CRC patients (37,39).…”
Section: Stat1/3 As Yin/yang Antagonistsmentioning
confidence: 56%
“…In contrast, others reported on STAT3 as a determinant of positive outcome in intestinal tumour progression (37,38). Moreover, we could show recently that absence of STAT1 and/ or STAT3 proteins is correlated with shorter survival of CRC patients (37,39). We performed a systematic study to shed light on the functional interplay and the tumour growth-associated roles of STAT1/3 in CRC progression.…”
Section: Stat1/3 As Yin/yang Antagonistsmentioning
confidence: 96%